MANIFESTASI MASYARAKAT BERAGAMA DAN IMPLEMENTASI NILAI PANCASILA DALAM TRADISI BERSIH DESA BULAN MUHARAM DI BLITAR - Arik Cahyani; Chandra, Afry Adi; Oktafiana, Andi Nur (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2023)
ABSTRACTThe primary objective of this study is to explore the manifes-tations of religious communities and the implementation of Pancasila values within the